Modernization Of Educational Activities and Their Formation - Tadjiyeva Moxiraxon Djaxongirovna (Genius Journals, 2022)
Research conducted by many psychologists, as well as Uzbek psychologists, allows us to identify the most essential qualities for modern teachers. In this case, the professogram of the teaching profession (a short and comprehensive document that is systematized, studied by labor psychologists and intended for use in future practice) is called a professogram.
Keywords: Professional skills; analysis; teacher; practice